2018
DOI: 10.14505//jarle.v8.8(30).25
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Support of Organizations Implementing Innovative Activities Investment Attractiveness Estimation

Abstract: Development of modern economy in the context of globalization and business integration, competition stiffening in virtually all sectors of the national economy, makes it impossible to develop large enterprises without significant investment infusions. Therefore, the topic is relevant and necessary for consideration. The main goal of the work is to disclose various aspects of methodological support for assessing the investment attractiveness of innovative companies that are necessary to meet the information nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In this case, the recommended form of cooperation is production cooperation, when each of the partners fulfills its share of work within the framework of a single production cycle (Plaskova et al, 2017;Prodanova et al, 2019aProdanova et al, , 2019b). Such a system of partnerships is highly effective because it leads to a complete coincidence of the economic interests of partners, thus, they will act so that the goods can be sold at the highest possible price, everyone will be interested in the quality and other indicators that are important for the market.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the recommended form of cooperation is production cooperation, when each of the partners fulfills its share of work within the framework of a single production cycle (Plaskova et al, 2017;Prodanova et al, 2019aProdanova et al, , 2019b). Such a system of partnerships is highly effective because it leads to a complete coincidence of the economic interests of partners, thus, they will act so that the goods can be sold at the highest possible price, everyone will be interested in the quality and other indicators that are important for the market.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have identified the effects of resource use optimization in the conditions of market relations transformation [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]:…”
Section: Resultsmentioning
confidence: 99%
“…. In the implementation of programs, the state usually plays the leading role, since the need for rapid concentration of significant resources, the complexity of the problem and the uncertainty of economic efficiency make direct regulation expedient with the supporting role of market-based instruments (Ponomareva et al, 2019;Ivanova, et al, 2019;Plaskova et al, 2017). In Russia, federal targeted programs are necessary for the rehabilitation of ecological disaster zones, the protection of especially valuable natural objects (Lake Baikal, river systems, sea basins), and the fulfillment of international obligations (protection of the ozone layer, greenhouse gases, biodiversity conservation).…”
Section: Resultsmentioning
confidence: 99%